Model Predictive Convex Programming for Constrained Vehicle Guidance - Hong, Haichao; Maity, Arnab; Holzapfel, Florian; Tang, Shengjing (IEEE transactions on aerospace and electronic systems, 2019)
A new model predictive convex programming is proposed in this paper for state and input constrained vehicle guidance design. The proposed method defines a convex optimization framework considering a flexibly designed cost function subject to inequality constraints and a sensitivity relation between state increments and input corrections. This formulated convex optimization problem can be solved in a computationally efficient manner. Simulation studies of nonlinear missile and aircraft landing guidance problems demonstrate the effectiveness of the proposed approach.